REORIENTASI PERTANGGUNGJAWABAN KLIEN DALAM PERJANJIAN FACTORING BAGI INDUSTRI KECIL - Malikhatun, Siti (Fakultas Hukum, Universitas Diponegoro, 2018)
Business development by business actors is using factoring financing. The factoring agreement raises the accountability of the parties, one of whom is the client. This study aims to reveal the client's accountability in the factoring agreement and how it should be in the future in order to realize justice for the parties. The research method used is mixed methode, with legal pluralism approach. It is known that the accountability of the client that is visible from his rights and obligations is inconsistent with the principles of factoring. Keywords: Factoring, agreements, clients